(untitled) (Eurasian Research Bulletin, 2022)
The light industry, and especially the textile industry, is increasingly attracting the attention of foreign investors. And this is no coincidence, because today a third of all workers employed in the industrial sector are concentrated in it. Along with an increase in the share of processed cotton fiber, the leadership of the republic set before the workers of the textile industry a responsible task to improve the quality of products, increase export potential. This decision required the reconstruction and modernization of existing enterprises and the construction of new ones. In the article, the analysis of the prospects for the development of double-patterned weaving constructions with geometric patterned press ring elements was highlighted.